2016
DOI: 10.1093/bioinformatics/btw797
|View full text |Cite
|
Sign up to set email alerts
|

VarMatch: robust matching of small variant datasets using flexible scoring schemes

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…A variety of approaches have been recently developed to address the challenges in variant representation. [9][10][11]21,22 Real Time Genomics (RTG) developed the comparison tool vcfeval, which introduced the idea of comparing variants at the level of the genomic haplotypes that the variants represent as a way to overcome the problems associated with comparing complex variants, where alternative yet equivalent variant representations can confound direct comparison methods. 9 Variant "normalization" tools help to represent variants in a standardized way (e.g., by left-shifting indels in repeats), but they demonstrated that "variant normalization" approaches alone were not able to reconcile different representations of many complex variants.…”
Section: Variant Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of approaches have been recently developed to address the challenges in variant representation. [9][10][11]21,22 Real Time Genomics (RTG) developed the comparison tool vcfeval, which introduced the idea of comparing variants at the level of the genomic haplotypes that the variants represent as a way to overcome the problems associated with comparing complex variants, where alternative yet equivalent variant representations can confound direct comparison methods. 9 Variant "normalization" tools help to represent variants in a standardized way (e.g., by left-shifting indels in repeats), but they demonstrated that "variant normalization" approaches alone were not able to reconcile different representations of many complex variants.…”
Section: Variant Representationmentioning
confidence: 99%
“…Similarly, VarMatch was developed to resolve alternate representations of complex variants, with additional ability to tune the matching parameters depending on the application. 10 Finally, hap.py includes a comparison tool to perform haplotype-based comparison of complex variants in addition to sophisticated functionality to stratify variant calls by type or region. 21 Note that representations include phasing information in these examples where it is necessary to unambiguously describe the variant.…”
Section: Variant Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simplistic comparison methods that do not account for different representations of complex variants can cause methods that represent variants similarly to the benchmark to appear better than methods that represent variants in a different way. 20,21 The Global Alliance for Genomics and Health Benchmarking Team has developed sophisticated methods that account for these differences as long as the complex variant is fully called correctly in both the benchmark and test callsets. 8 Differences in representation can make up a significant fraction of putative FPs and FNs, so it is important to use these tools.…”
Section: Performance Metrics Can Vary Significantly When Comparing Tomentioning
confidence: 99%
“…The "strict matching" approach matches two indels if they share the same position, reference, and alternate alleles in two different entries in the VCF file. However, as demonstrated in [3], this approach fails to find equivalent indels that are not identical. The "distance based approach" treats two indels as equivalent if both have the same length 3 and occur within a certain distance such as ± 5 bp [5] or ± 25 bp [6].…”
Section: Introductionmentioning
confidence: 99%